2x+8=6-5x

Simple and best practice solution for 2x+8=6-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+8=6-5x equation:


Simplifying
2x + 8 = 6 + -5x

Reorder the terms:
8 + 2x = 6 + -5x

Solving
8 + 2x = 6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
8 + 2x + 5x = 6 + -5x + 5x

Combine like terms: 2x + 5x = 7x
8 + 7x = 6 + -5x + 5x

Combine like terms: -5x + 5x = 0
8 + 7x = 6 + 0
8 + 7x = 6

Add '-8' to each side of the equation.
8 + -8 + 7x = 6 + -8

Combine like terms: 8 + -8 = 0
0 + 7x = 6 + -8
7x = 6 + -8

Combine like terms: 6 + -8 = -2
7x = -2

Divide each side by '7'.
x = -0.2857142857

Simplifying
x = -0.2857142857

See similar equations:

| 1/3(5-x)=6 | | -4(b+5)=-b+7 | | 12y-7y=18 | | y=5x-2-3x+5 | | 6/2x15 | | 8(u+4)-4(u+9)=8 | | 90=3(6x-6) | | 9m+7=5m+27 | | 5(f-1)=15 | | 6z=(0.5z-8) | | -96=2-7(2-4n) | | 4(2y+1)-7y=18 | | 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 | | 5p-2q=23 | | 3(4s+4)=7 | | 4/3x3.14x343= | | 6(2l+2)=132 | | -1+3(7+3x)=83 | | 7m-3+2m=13+m | | sinx=1.5 | | 13x+5y=179 | | 25=40+3x | | 6(21+2)=132 | | 144=6(5x+4) | | 15x+7y=193 | | 3(a-2)=60 |

Equations solver categories